Industrial waste residue ecological and environmentally friendly permeable brick and preparation method thereof

By using industrial waste slag and special binder, an ecological and environmentally friendly permeable brick with high compressive strength, good wear resistance and excellent permeable performance was prepared, which solved the compressive strength, wear resistance and existing permeable bricks. The shortcomings in environmental protection have achieved environmental protection, energy saving and production costs.

CN119330652BActive Publication Date: 2025-02-25SHANDONG ZHAOHE ENVIRONMENTAL PROTECTION BUILDING MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411900953.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-02-25
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing permeable bricks have shortcomings in compressive strength, wear resistance and environmental protection, especially the weather resistance of polymer permeable concrete, and the production cost of sintered permeable bricks is high.

Method used

Using industrial waste slag as the main raw material, a kind of industrial waste slag ecologically friendly water-friendly brick is prepared through specific binder preparation methods and process flows. The binder is reacted by the reaction of DMF, toluene 2,6-diisocyanate, PEG800 and other materials to form an intermediate with high adhesive properties and modified resin, and finally reacts with hydroxyl-terminated polydimethylsiloxane to prepare A binder with excellent adhesive properties is produced.

Benefits of technology

It realizes the high compressive strength, good wear resistance and excellent water permeability of permeable bricks, while reducing dependence on natural resources, reducing production costs, and has the characteristics of environmental protection and beauty.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_12
    Figure SMS_12
Patent Text Reader

Abstract

The invention discloses an industrial waste residue eco-friendly water-permeable brick and a preparation method thereof, and relates to the technical field of water-permeable bricks. The eco-friendly water-permeable bricks include the following raw materials in parts by weight: industrial waste residue: 80-100 parts, cement: 10-12 parts, deionized water: 30-50 parts, filler: 10-12 parts, surfactant: 2-5 parts, binder: 5-10 parts. The present invention prepares a transparent colloidal solid by toluene 2,6-diisocyanate and PEG800, and then reacts the transparent colloidal solid with 1,2,4-tricarboxylic anhydride to prepare intermediate 1, and grafts intermediate 1 onto 3,3'5,5'-tetramethylbiphenyl bisphenol diglycidyl ether through a ring-opening reaction, and finally grafts organosilicon onto a modified resin to prepare a binder with strong adhesion. The eco-friendly water-permeable bricks prepared by the present invention have the characteristics of good compressive strength, high water permeability coefficient and good wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of permeable bricks, and in particular to an industrial waste residue ecological and environmentally friendly permeable brick and a preparation method thereof. Background Art

[0002] With the development of industry, the amount of industrial waste is increasing day by day, especially in industries such as metallurgy and thermal power generation, which have the largest emissions. The amount of industrial waste is huge, the types are numerous, the composition is complex, and it is quite difficult to handle. Solid waste disposal and resource utilization are one of the most important bottlenecks in the development of coal, electricity, energy and chemical industries in many provinces. Industrial waste can be turned into industrial raw materials or energy through proper process treatment. Some industrial waste has been made into a variety of products, such as cement, concrete aggregates, bricks and tiles, fibers, cast stone and other building materials.

[0003] With my country's increasing attention to environmental issues, permeable pavements have also been promoted and applied in large and medium-sized cities. At present, the permeable pavement bricks used in my country mainly include cement-based permeable concrete bricks, polymer permeable concrete bricks, and sintered permeable bricks. Among them, polymer permeable concrete uses asphalt or polymer resin as a binder, which has poor weather resistance and is easy to age under the influence of the atmospheric environment. It is easy to soften and flow when the temperature rises, which affects the permeability; the sintering process of sintered permeable bricks requires energy consumption and is costly, and is only suitable for high-end floor paving with small amounts. Therefore, it is particularly important to develop a permeable brick with good permeability, compressive strength, wear resistance, anti-slip, environmental protection and beauty.

[0004] A Chinese invention patent with publication number CN107324747A discloses a permeable brick and a preparation method thereof. The permeable brick is made of the following raw materials in parts by weight: 100-140 parts of industrial waste residue, 40-60 parts of urban waste residue, 25-35 parts of desulfurized gypsum, 18-22 parts of modified bentonite, 35-45 parts of surfactant, and 20-30 parts of adhesive. The permeable brick has good wear resistance and water retention, but its compressive strength is poor. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide an industrial waste residue ecological and environmentally friendly permeable brick and a preparation method thereof.

[0006] To achieve the above object, the present invention is implemented through the following technical solutions:

[0007] An industrial waste residue eco-friendly water-permeable brick, the eco-friendly water-permeable brick comprises the following raw materials in parts by weight: industrial waste residue: 80-100 parts, cement: 10-12 parts, deionized water: 30-50 parts, filler: 10-12 parts, surfactant: 2-5 parts, binder: 5-10 parts;

[0008] The binder is prepared by the following method:

[0009] S1: Under nitrogen protection, DMF and toluene 2,6-diisocyanate are added to the reactor in sequence, stirred and dissolved, and the temperature is raised to 50-70°C, and then PEG800 is slowly added dropwise. After the addition, the catalyst dibutyltin dilaurate is added, and the reaction is carried out for 4-6 hours. After post-treatment, a transparent colloidal solid is obtained. The reaction equation is shown as follows: ;

[0010] S2: Under nitrogen protection, DMF and transparent colloidal solid are added to the reactor in sequence, stirred, heated to 80-90°C, and then 1,2,4-benzenetricarboxylic anhydride is slowly added dropwise, and the temperature is continued to rise to 100-120°C, reacted for 4-6h, and post-treated to obtain intermediate 1, the reaction equation of which is shown as follows:

[0011] ;

[0012] S3: DMF, intermediate 1 and 3,3'5,5'-tetramethylbiphenyl bisphenol diglycidyl ether are added to the reactor in sequence, stirred, heated to 80-120°C, reacted for 4-6h, cooled to 60-80°C, and triethylamine was added for neutralization to obtain intermediate 2. The reaction equation is as follows:

[0013] ;

[0014] S4: Toluene, intermediate 2 and hydroxyl-terminated polydimethylsiloxane are added to the reactor in sequence, stirred, heated to 90-120°C, and then dibutyltin dilaurate is added, reacted for 8-10 hours, and post-treated to obtain a binder. The reaction equation is shown as follows:

[0015] ;

[0016] in, represent:

[0017] ;

[0018] represent:

[0019] ;

[0020] represent:

[0021] ;

[0022] M stands for:

[0023] ;

[0024] m, o, r, p, q, s, t are natural numbers.

[0025] In the step S1, the feed mass ratio of DMF, toluene 2,6-diisocyanate, PEG800, and dibutyltin dilaurate is 30:(8-10):(4-6):(0.01-0.03).

[0026] In the step S2, the mass ratio of DMF, 1,2,4-benzenetricarboxylic anhydride and transparent colloidal solid is 50:(10-12):(4-6).

[0027] In the step S3, the mass ratio of DMF, 3,3'5,5'-tetramethylbiphenyl bisphenol diglycidyl ether and intermediate 1 is 50:(8-12):(15-18).

[0028] In the step S4, the feed mass ratio of toluene, intermediate 2, hydroxyl-terminated polydimethylsiloxane and dibutyltin dilaurate is 50:(4-6):(12-15):(0.03-0.05).

[0029] The filler is one of silicon dioxide and bentonite.

[0030] The surfactant is one of sodium lauryl sulfate, sodium fatty alcohol polyoxyethylene ether sulfate and sodium fatty acid methyl ester sulfonate.

[0031] A method for preparing an industrial waste residue ecological and environmentally friendly permeable brick comprises the following steps:

[0032] Weigh by weight: industrial waste residue: 80-100 parts, cement: 10-12 parts, deionized water: 30-50 parts, filler: 10-12 parts, surfactant: 2-5 parts, binder: 5-10 parts;

[0033] (2) Industrial waste residue, cement and surfactant are mixed evenly, and then a binder, a filler and deionized water are added and stirred, the mixed material is spread in a mold, and the mold is placed in a pressing machine for vibration pressing to obtain a semi-finished permeable brick; the semi-finished permeable brick is placed in a curing room for static curing for 8 days, and then the mold is removed, and the permeable brick is sprayed with water for humidification curing for 28 days to obtain a high-strength ecological and environmentally friendly permeable brick.

[0034] Due to the adoption of the above technical solution, the beneficial effects of the present invention include:

[0035] (1) The present invention prepares a transparent colloidal solid by using toluene 2,6-diisocyanate and PEG800, then reacts the transparent colloidal solid with 1,2,4-benzenetricarboxylic anhydride to prepare an intermediate 1, grafts the intermediate 1 onto 3,3'5,5'-tetramethylbiphenyl bisphenol diglycidyl ether through a ring-opening reaction, and finally grafts silicone onto a modified resin to prepare a strong adhesive.

[0036] (2) The present invention uses industrial waste instead of natural raw materials to process permeable bricks, which reduces the pollution caused by waste to the environment, reduces the exploitation of natural resources, saves energy, and reduces the production cost of permeable bricks.

[0037] (3) In the binder prepared by the present invention, hydroxyl-terminated polydimethylsiloxane reacts with hydroxyl groups on the modified resin to synthesize siloxane-modified resin. In the organosilicon-modified resin, an interpenetrating network structure connected by Si-OC bonds is formed between siloxane and the resin, thereby improving the poor compatibility between siloxane and the resin. At the same time, a flexible Si-O bond is introduced, which can make the polymer chain segment rotate more easily, reduce the internal stress of the resin, and thus greatly improve the fracture toughness of the resin, so that the prepared permeable brick has good mechanical strength.

[0038] (4) The adhesive prepared by the present invention contains a large amount of urethane groups and a special three-dimensional network structure, which gives it excellent bonding properties. The use of a reasonably proportioned adhesive allows the various components of the raw materials to be effectively combined to form a permeable brick with a high porosity structure, thereby improving the permeability coefficient of the permeable brick. DETAILED DESCRIPTION

[0039] The invention will be further described below in conjunction with the embodiments, but the invention is not limited to these embodiments.

[0040] Example 1

[0041] Preparation of binder:

[0042] S1: Under nitrogen protection, 300g DMF and 80g toluene 2,6-diisocyanate were added to the reactor in sequence, stirred and dissolved, heated to 50°C, and then 40g PEG800 was slowly added dropwise. After the addition, 0.1g catalyst dibutyltin dilaurate was added. The reaction was continued for 6h, and then 500ml ice water was added for precipitation and filtration. The mixture was vacuum dried at 50°C for 6h to obtain a transparent colloidal solid.

[0043] S2: Under nitrogen protection, 500 g of DMF and 40 g of a transparent colloidal solid were added to the reactor in sequence, stirred, heated to 80°C, and then 100 g of 1,2,4-tricarboxylic anhydride was slowly added dropwise, and the temperature was continued to rise to 100°C, reacted for 6 h, and distilled at 50°C under reduced pressure for 3 h to obtain intermediate 1;

[0044] S3: 500g DMF, 150g intermediate 1 and 80g 3,3'5,5'-tetramethylbiphenyl bisphenol diglycidyl ether were added to the reactor in sequence, stirred, heated to 80°C, reacted for 6h, cooled to 60°C, added 150ml triethylamine for neutralization, and distilled at 60°C under reduced pressure for 5h to obtain intermediate 2;

[0045] S4: 500g toluene, 40g intermediate 2 and 120g hydroxyl-terminated polydimethylsiloxane were added into the reactor in sequence, stirred, and heated to 90°C. Then, 0.3g dibutyltin dilaurate was added and reacted for 10h. After the reaction, the temperature was cooled to room temperature, 200g deionized water was added, and the mixture was stirred at high speed (1000r / min) for emulsification for 1h to obtain the binder.

[0046] Example 2

[0047] Preparation of binder:

[0048] S1: Under nitrogen protection, 300g DMF and 90g toluene 2,6-diisocyanate were added to the reactor in sequence, stirred and dissolved, heated to 60°C, and then 50g PEG800 was slowly added dropwise, and 0.2g catalyst dibutyltin dilaurate was added after the addition, and the reaction was continued for 5h, and then 500ml ice water was added for precipitation and filtration, and vacuum dried at 60°C for 5h to obtain a transparent colloidal solid;

[0049] S2: Under nitrogen protection, 500 g of DMF and 50 g of a transparent colloidal solid were added to the reactor in sequence, stirred, heated to 85°C, and then 110 g of 1,2,4-tricarboxylic anhydride was slowly added dropwise, and the temperature was continued to rise to 110°C, reacted for 5 h, and distilled at 60°C under reduced pressure for 2 h to obtain intermediate 1;

[0050] S3: 500g DMF, 170g intermediate 1 and 100g 3,3'5,5'-tetramethylbiphenyl bisphenol diglycidyl ether were added to the reactor in sequence, stirred, heated to 100°C, reacted for 5h, cooled to 70°C, added 150ml triethylamine for neutralization, and distilled at 70°C under reduced pressure for 4h to obtain intermediate 2;

[0051] S4: 500g toluene, 50g intermediate 2 and 130g hydroxyl-terminated polydimethylsiloxane were added into the reactor in sequence, stirred, and heated to 105°C. Then, 0.4g dibutyltin dilaurate was added and reacted for 9h. After the reaction, the temperature was cooled to room temperature, 200g deionized water was added, and the mixture was stirred at high speed (1000r / min) for emulsification for 1h to obtain the binder.

[0052] Example 3

[0053] Preparation of binder:

[0054] S1: Under nitrogen protection, 300g DMF and 100g toluene 2,6-diisocyanate were added to the reactor in sequence, stirred to dissolve, heated to 70°C, and then 60g PEG800 was slowly added dropwise. After the addition, 0.3g catalyst dibutyltin dilaurate was added. The reaction was continued for 4h, and then 500ml ice water was added for precipitation and filtration. The mixture was vacuum dried at 70°C for 4h to obtain a transparent colloidal solid.

[0055] S2: Under nitrogen protection, 500 g of DMF and 60 g of a transparent colloidal solid were added to the reactor in sequence, stirred, heated to 90°C, and then 120 g of 1,2,4-benzenetricarboxylic anhydride was slowly added dropwise, and the temperature was continued to rise to 120°C, reacted for 4 h, and distilled at 70°C under reduced pressure for 1 h to obtain intermediate 1;

[0056] S3: 500g DMF, 180g intermediate 1 and 120g 3,3'5,5'-tetramethylbiphenyl bisphenol diglycidyl ether were added to the reactor in sequence, stirred, heated to 120°C, reacted for 4h, cooled to 80°C, added 150ml triethylamine for neutralization, and distilled at 80°C under reduced pressure for 3h to obtain intermediate 2;

[0057] S4: 500g toluene, 60g intermediate 2 and 150g hydroxyl-terminated polydimethylsiloxane were added into the reactor in sequence, stirred, and heated to 120°C. Then, 0.5g dibutyltin dilaurate was added and reacted for 8h. After the reaction, the temperature was cooled to room temperature, 200g deionized water was added, and the mixture was stirred at high speed (1000r / min) for emulsification for 1h to obtain the binder.

[0058] Example 4

[0059] Preparation of eco-friendly permeable bricks:

[0060] S1: weigh industrial waste residue: 800 g, cement: 100 g, deionized water: 300 g, filler (silicon dioxide): 100 g, surfactant (sodium dodecyl sulfate): 20 g, binder (prepared in Example 1): 50 g;

[0061] S2: Add industrial waste residue, cement and surfactant into a sand mixer and stir for 20 minutes at a stirring speed of 200r / min. After mixing evenly, add binder, filler and deionized water and mix and stir for 10 minutes at a stirring speed of 300r / min. Spread the mixed material in a mold, place the mold in a press for vibration pressing. During the vibration pressing process, the pressure is 20MPa, the pressing time is 10s, and the vibration frequency is 60Hz to obtain a semi-finished permeable brick; place the semi-finished permeable brick in a curing room for static curing for 8 days, then remove the mold, and spray the permeable brick for humidification curing for 28 days to obtain a high-strength, ecological and environmentally friendly permeable brick with a size of 200mm×100mm×60mm.

[0062] Example 5

[0063] Preparation of eco-friendly permeable bricks:

[0064] S1: weigh industrial waste residue: 900 g, cement: 110 g, deionized water: 400 g, filler (bentonite): 110 g, surfactant (sodium fatty alcohol polyoxyethylene ether sulfate): 35 g, binder (prepared in Example 2): 80 g;

[0065] S2: Add industrial waste residue, cement and surfactant into a sand mixer and stir for 20 minutes at a stirring speed of 200r / min. After mixing evenly, add binder, filler and deionized water and mix and stir for 10 minutes at a stirring speed of 300r / min. Spread the mixed material in a mold, place the mold in a press for vibration pressing. During the vibration pressing process, the pressure is 20MPa, the pressing time is 10s, and the vibration frequency is 60Hz to obtain a semi-finished permeable brick; place the semi-finished permeable brick in a curing room for static curing for 8 days, then remove the mold, and spray the permeable brick for humidification curing for 28 days to obtain a high-strength, ecological and environmentally friendly permeable brick with a size of 200mm×100mm×60mm.

[0066] Example 6

[0067] Preparation of eco-friendly permeable bricks:

[0068] S1: weigh industrial waste residue: 1000 g, cement: 120 g, deionized water: 500 g, filler (silicon dioxide): 120 g, surfactant (sodium fatty acid methyl ester sulfonate): 50 g, binder (prepared in Example 3): 100 g;

[0069] S2: Add industrial waste residue, cement and surfactant into a sand mixer and stir for 20 minutes at a stirring speed of 200r / min. After mixing evenly, add binder, filler and deionized water and mix and stir for 10 minutes at a stirring speed of 300r / min. Spread the mixed material in a mold, place the mold in a press for vibration pressing. During the vibration pressing process, the pressure is 20MPa, the pressing time is 10s, and the vibration frequency is 60Hz to obtain a semi-finished permeable brick; place the semi-finished permeable brick in a curing room for static curing for 8 days, then remove the mold, and spray the permeable brick for humidification curing for 28 days to obtain a high-strength, ecological and environmentally friendly permeable brick with a size of 200mm×100mm×60mm.

[0070] Comparative Example 1

[0071] The raw material composition and process of the eco-friendly permeable brick are basically the same as those of Example 5, except that no binder is added to the composition.

[0072] Comparative Example 2

[0073] The raw material composition and process of the eco-friendly permeable brick are basically the same as those of Example 5, except that the binder is replaced by an equal weight of the intermediate 2 prepared in step S3 of Example 2.

[0074] Comparative Example 3

[0075] The raw material composition and process of the eco-friendly permeable bricks are basically the same as those of Example 5, except that the binder is replaced with an equal weight of polyurethane binder.

[0076] Comparative Example 4

[0077] The raw material composition and process of the eco-friendly permeable brick are basically the same as those in Example 5, except that the binder is replaced by 22 g of intermediate 2 (prepared in step S3 of Example 2) and 58 g of hydroxyl-terminated polydimethylsiloxane.

[0078] Comparative Example 5

[0079] The preparation method of ecological and environmentally friendly permeable bricks is:

[0080] S1: weigh industrial waste residue: 900 g, cement: 110 g, deionized water: 400 g, filler (bentonite): 110 g, surfactant (sodium fatty alcohol polyoxyethylene ether sulfate): 35 g, binder (prepared in Example 2): 30 g;

[0081] S2: Add industrial waste residue, cement and surfactant into a sand mixer and stir for 20 minutes at a stirring speed of 200r / min. After mixing evenly, add binder, filler and deionized water and mix and stir for 10 minutes at a stirring speed of 300r / min. Spread the mixed material in a mold, place the mold in a press for vibration pressing. During the vibration pressing process, the pressure is 20MPa, the pressing time is 10s, and the vibration frequency is 60Hz to obtain a semi-finished permeable brick; place the semi-finished permeable brick in a curing room for static curing for 8 days, then remove the mold, and spray the permeable brick for humidification curing for 28 days to obtain a high-strength, ecological and environmentally friendly permeable brick with a size of 200mm×100mm×60mm.

[0082] Comparative Example 6

[0083] The recycled permeable brick is made using the raw material composition and process of Example 8 of the Chinese invention patent with publication number CN107324747A.

[0084] The main components of the industrial waste slag used in the examples and comparative examples of the present application are fly ash (40wt%) and slag (60wt%). The main components of the fly ash are silicon dioxide (54.9wt%), aluminum oxide (26.4wt%), ferric oxide (11.2wt%), calcium oxide (5.8wt%), etc., and the particle size is mainly concentrated in the range of 0.45-0.85mm. The main components of the slag are silicon dioxide (31.9wt%), calcium oxide (36.2wt%), aluminum oxide (17. 2wt%), magnesium oxide (13.5wt%), with particle size concentrated in 1-3mm; cement is road silicate cement 42.5 grade (codenamed P.R7.5), purchased from Shanxi Excellence Cement Co., Ltd.; the model of polyurethane binder is K-6502, purchased from Guangdong Evergrande New Materials Technology Co., Ltd.; the model of bentonite is Bentone38, purchased from Dachanghua Jiahui Zhengxing Chemical (Shanghai) Co., Ltd.; the model of silicon dioxide is HL-200, purchased from Hubei Huifu Nanomaterials Co., Ltd.

[0085] The eco-friendly permeable bricks prepared in Examples 4-6 of the present application and Comparative Examples 1-6 were tested for compressive strength, flexural strength, wear resistance and water permeability coefficient. The test results are shown in Table 1.

[0086] According to GB / T25993-2010 "Permeable Pavement Bricks and Permeable Road Slabs", permeability coefficient and flexural strength tests were carried out.

[0087] Wear resistance and compressive strength tests were carried out according to JC / T945-2005 "Permeable Bricks".

[0088] Table 1

[0089]

[0090] It can be seen from Table 1 that the eco-friendly permeable bricks prepared in Examples 4-6 of the present application have excellent compressive strength, wear resistance and water permeability coefficient.

[0091] Comparative Example 1 is a comparative example prepared without adding a binder. From the data in Table 1, it can be seen that its compressive strength is 30.1 MPa, the grinding pit length is 28.4 mm, and the water permeability coefficient is 15.7 mm / s.

[0092] The binder added in Comparative Example 2 is the intermediate 2 prepared in step S3 of Example 2. As can be seen from Table 1, its compressive strength is 37.9 MPa, the grinding pit length is 27.6 mm, and the water permeability coefficient is 16.6 mm / s.

[0093] The binder added in Comparative Example 3 is a polyurethane binder. As can be seen from Table 1, its compressive strength is 42.6 MPa, the grinding pit length is 25.3 mm, and the water permeability coefficient is 19.3 mm / s.

[0094] The binders added in Comparative Example 4 are 22 g of intermediate 2 (prepared in step S3 of Example 2) and 58 g of hydroxyl-terminated polydimethylsiloxane. As can be seen from Table 1, its compressive strength is 40.5 MPa, the grinding pit length is 26.1 mm, and the water permeability coefficient is 19.0 mm / s.

[0095] The weight of the binder added in Comparative Example 5 is 30 g. As can be seen from Table 1, its compressive strength is 43.9 MPa, the grinding pit length is 24.8 mm, and the water permeability coefficient is 23.9 mm / s.

[0096] Comparative Example 6 is a recycled permeable brick made with the raw material composition and process in Example 8 of the Chinese invention patent CN107324747A. As can be seen from Table 1, its compressive strength is 36.7 MPa, the grinding pit length is 23.7 mm, and the permeability coefficient is 17.1 mm / s.

[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in the field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. An industrial waste residue ecological and environmentally friendly permeable brick, characterized in that: The eco-friendly water-permeable bricks include the following raw materials in parts by weight: Industrial waste residue: 80-100 parts, Cement: 10-12 parts, Deionized water: 30-50 parts, Filling: 10-12 portions, Surfactant: 2-5 parts, Binder: 5-10 parts; The binder is prepared by the following method: S1: Under nitrogen protection, DMF and toluene 2,6-diisocyanate are added to the reactor in sequence, stirred and dissolved, and the temperature is raised to 50-70°C, and then PEG800 is slowly added dropwise, and after the addition, the catalyst dibutyltin dilaurate is added, and the reaction is carried out for 4-6 hours. After post-treatment, a transparent colloidal solid is obtained; S2: Under nitrogen protection, DMF and a transparent colloidal solid are added to the reactor in sequence, stirred, heated to 80-90°C, and then 1,2,4-benzenetricarboxylic anhydride is slowly added dropwise, and the temperature is continued to rise to 100-120°C, reacted for 4-6 hours, and post-treated to obtain intermediate 1; S3: DMF, intermediate 1 and 3,3'5,5'-tetramethylbiphenyl bisphenol diglycidyl ether are added to the reactor in sequence, stirred, heated to 80-120°C, reacted for 4-6h, cooled to 60-80°C, and triethylamine was added for neutralization to obtain intermediate 2; S4: Toluene, intermediate 2 and hydroxyl-terminated polydimethylsiloxane are added to the reactor in sequence, stirred, heated to 90-120° C., and then dibutyltin dilaurate is added, reacted for 8-10 hours, and post-treated to obtain a binder.

2. The industrial waste residue ecological and environmentally friendly permeable brick according to claim 1, characterized in that: In the step S1, the feed mass ratio of DMF, toluene 2,6-diisocyanate, PEG800, and dibutyltin dilaurate is 30:(8-10):(4-6):(0.01-0.03).

3. The industrial waste residue ecological and environmentally friendly permeable brick according to claim 1, characterized in that: In the step S2, the mass ratio of DMF, 1,2,4-benzenetricarboxylic anhydride and transparent colloidal solid is 50:(10-12):(4-6).

4. The industrial waste residue ecological and environmentally friendly permeable brick according to claim 1, characterized in that: In the step S3, the mass ratio of DMF, 3,3'5,5'-tetramethylbiphenyl bisphenol diglycidyl ether and intermediate 1 is 50:(8-12):(15-18).

5. The industrial waste residue ecological and environmentally friendly permeable brick according to claim 1, characterized in that: In the step S4, the feed mass ratio of toluene, intermediate 2, hydroxyl-terminated polydimethylsiloxane and dibutyltin dilaurate is 50:(4-6):(12-15):(0.03-0.05).

6. The industrial waste residue ecological and environmentally friendly permeable brick according to claim 1, characterized in that: The filler is one of silicon dioxide and bentonite.

7. The industrial waste residue ecological and environmentally friendly permeable brick according to claim 1, characterized in that: The surfactant is one of sodium lauryl sulfate, sodium fatty alcohol polyoxyethylene ether sulfate and sodium fatty acid methyl ester sulfonate.

8. A method for preparing the industrial waste residue ecological and environmentally friendly permeable brick according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Weigh by weight: industrial waste residue: 80-100 parts, cement: 10-12 parts, deionized water: 30-50 parts, filler: 10-12 parts, surfactant: 2-5 parts, binder: 5-10 parts; (2) Industrial waste slag, cement and surfactant are mixed evenly, and then a binder, a filler and deionized water are added and stirred, the mixed material is spread in a mold, and the mold is placed in a pressing machine for vibration pressing to obtain a semi-finished permeable brick; the semi-finished permeable brick is placed in a curing room for static curing for 8 days, and then the mold is removed, and the permeable brick is sprayed with water for humidification curing for 28 days to obtain an industrial waste slag ecological and environmentally friendly permeable brick.

Citation Information

Patent Citations

  • Novel pervious brick and preparation method

    CN107324747A

  • Dual component (aqueous) hybrid reactive resin system, method for production and use thereof

    CN101410428A

  • High-strength environment-friendly water permeable brick

    CN115893947A